Spatial Distribution and Density of Tigers with Ref'erence to the Status of Biotic Pressure and Protection Accorded in Different Habitats of Melghat Tiger Reserve - Choudhary, Ramanuj (Indian Forester, 2005)
The Melghat Tiger Reserve, one of the nine prime 'Tiger Reserves' covered under 'Project Tiger' in 1973, has three different areas which received varying degree of protection for its habitats. The study reveals that the spatial distribution and density of tigers as well as its prey biomass to a large extent is dependent on elimination of human uses and disturbances, and more density is observed as tbe ecosystem comes closer to the natural functioning devoid of human pressures. Tbe 'core' area i.e. Gugamal National Park of the Reserve, which is free from all disturbances and is almost close to natural functioning has displayed tiger density of about 7 tigers per 100 km2, whereas, the Melghat Sanctuary with some disturbances in term of visitation and other human uses througb presence of villagers shows a density of 4 tigers per 100 km2. In contrast, the 'Multiple Use Area' which is dominated by villages and their cattle, though it is part of MTR, shows a dismal density of only 2 to 3 tigers per 100 km2. The recently extended buffer area which is newly declared as Wan, Ambabarwa and Narnala Sanctuaries has excessive human pressure and displays still low density of 1.5 tigers per 100 km2. The density of prey biomass shows significant variations being inversely proportional to the extent of biotic pressure. Tbe study reveals that human and cattle use must be eliminated from the area of the Reserve, if the area is to be managed as a Tiger Reserve in its true sense. The prospective estimate for tigers in MTR is put at 140 to 145, if human use is eliminated from the area, as compared to the present estimate of about 73 to 75.